2015
DOI: 10.1530/ec-15-0071
|View full text |Cite
|
Sign up to set email alerts
|

Serum adiponectin in HIV-1 and hepatitis C virus mono- and co-infected Kenyan injection drug users

Abstract: Adiponectin is an important marker of anthropometric profiles of adipose tissue. However, association of adiponectin and adiposity in HIV mono- and co-infected and hepatitis (HCV) injection drug users (IDUs) has not been elucidated. Therefore, the relationship of total adiponectin levels with anthropometric indices of adiposity was examined in HIV mono-infected (anti-retroviral treatment, ART-naive, n=16 and -experienced, n=34); HCV mono-infected, n=36; HIV and HCV co-infected (ART-naive, n=5 and -experienced,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…Consistent with our previous study ( 20 ), ART-naive ISUs had higher serum adiponectin levels suggesting that ART could directly or indirectly be causing lower levels of circulating adiponectin. Previous studies have associated ART use with low levels of serum adiponectin in HIV infected individuals.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with our previous study ( 20 ), ART-naive ISUs had higher serum adiponectin levels suggesting that ART could directly or indirectly be causing lower levels of circulating adiponectin. Previous studies have associated ART use with low levels of serum adiponectin in HIV infected individuals.…”
Section: Resultssupporting
confidence: 91%
“…However, there is limited data on how ADIPOQ gene polymorphisms influence these markers of disease progression among HIV-1 ISUs. We have previously shown that serum adiponectin levels are low in HIV-1 ART-naive ISUs from coastal Kenya ( 20 ). In addition, injection substance use leads to epigenetic modifications in gene expression and causes alterations in the DNA sequences ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Older antiretrovirals such as stavudine appear more likely to contribute to steatosis than the more commonly used agents today [ 75 ]. In addition, decreased adiponectin with HIV infection may contribute to the increased steatosis [ 76 ]. Thus, lipid deposition in the liver is increased in HIV infection.…”
Section: Introductionmentioning
confidence: 99%